Is Sensation-Seeking Always Bad? The Role of Sensation-Seeking in Predicting Individual Work Role Performance - Lelyana, Margaretha Langen Sekar; Siregar, Rury Ervina; Mustika, Martina Dwi (Universitas Islam Indonesia, 2022)
Sensation-seeking can be an outcome predictor in an organization when expressed through several social cognitive variables, such as emotional intelligence. Thus, the behavior generated by sensation-seeking can be more functional. The purpose of this study is to identify whether sensation-seeking can be expressed through emotional intelligence to predict individual performance. This study uses a quantitative design with a correlational strategy. The study participants were 167 Indonesian employees from three banking, oil and gas, and mining industries who filled out a questionnaire investigating their sensation-seeking, emotional intelligence, and individual performance. The questionnaires used Work Role Performance Scale and Learning Style Profiler. Data analysis was done by mediation process from Hayes. The results show that sensation-seeking and emotional intelligence directly predicts individual performance. However, indirect effect analysis proves that emotional intelligence cannot express sensation-seeking to predict individual performance. Thus, people who have high level of sensation-seeking not always bad because they can be an active learner also improve their work role performance in organization.